Intensity Control During Block-Periodized High-Intensity Training: Heart Rate and Lactate Concentration During Three Annual Seasons in World-Class Cross-Country Skiers - Trine Karlsen; Guro Strøm Solli; Guro Strøm Solli; Svein Tore Samdal; Øyvind Sandbakk (Frontiers Media S.A., 2020)
Purpose: To describe heart rate (HR) and blood lactate (Bla−) responses during high-intensity interval training (HIT) in a long-term block-periodized HIT regimen in world-class cross-country (XC) skiers.Methods: Data were collected in 14 world-class female XC skiers (aged 25 ± 5 years; body mass, 60.4 ± 6.5 kg; and maximal HR, 194 ± 8 beats · min−1) throughout three entire seasons. The HR and Bla− values were determined at the end of 572 intervals performed during 63 sessions and 17 HIT blocks utilizing different exercise modes: running, running with poles, and skiing (on-snow and roller ski) with classic and skating techniques.Results: The mean HR was 91 ± 3% of HRmax with a corresponding Bla− of 7.3 ± 2.1 mmol · L−1. The average HR and Bla− values were relatively similar across the different exercise modes, except for a lower HR (~90 vs. 92% of HRmax) for on-snow and roller ski classical skiing and lower Bla− values (5.9 vs. 7.0-7.8 mmol · L−1) for on-snow classical skiing compared to the other modes, both P < 0.05. An increase in HR and Bla− was observed from interval working periods 1 to 3 (90-92% of HRmax and 6.5-7.7 mmol · L−1) and further from 3 to 5 (92-93% of HRmax and 7.7-9.0 mmol · L−1), all P < 0.05.Conclusions: We describe long-term use of HIT-block periodization among world-class XC skiers who achieved target HR and Bla− levels in all six exercise modes employed. According to athletes and coaches, the key to successful blocks was intensity control to allow for high-quality HIT sessions throughout the entire HIT block.